2019
DOI: 10.1038/s41598-019-51614-x
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin A1 Alleviates Inflammatory Response induced by LPS through NF-κB, MAPK, and Nrf2/HO-1 Pathways in RAW264.7 cells

Abstract: Inflammation is a complex physiological process that poses a serious threat to people’s health. However, the potential molecular mechanisms of inflammation are still not clear. Moreover, there is lack of effective anti-inflammatory drugs that meet the clinical requirement. Procyanidin A1 (PCA1) is a monomer component isolated from Procyanidin and shows various pharmacological activities. This study further demonstrated the regulatory role of PCA1 on lipopolysaccharide (LPS)-stimulated inflammatory response and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 50 publications
3
59
1
1
Order By: Relevance
“…Under the stimulation of LPS, RAW26.7 cells activate inducible iNOS and COX enzyme systems, leading to cytokines like NO and PGE2 release [33]. Shan et al demonstrated that PCA1, an isomeride of PCA2, showed no effect on COX-2 and PGE2 in RAW264.7 cells [9]. However, in our study, PCA2 attenuated COX-2 expression and PGE2 release, which is different from PCA1 (Figs 1 and 2).…”
Section: Plos Onecontrasting
confidence: 57%
See 3 more Smart Citations
“…Under the stimulation of LPS, RAW26.7 cells activate inducible iNOS and COX enzyme systems, leading to cytokines like NO and PGE2 release [33]. Shan et al demonstrated that PCA1, an isomeride of PCA2, showed no effect on COX-2 and PGE2 in RAW264.7 cells [9]. However, in our study, PCA2 attenuated COX-2 expression and PGE2 release, which is different from PCA1 (Figs 1 and 2).…”
Section: Plos Onecontrasting
confidence: 57%
“…And B-type proanthocyanidins are bind together via C4β!C8, C4β!C6, C4α!C8 or C4α!C6 bonds, while A-type proanthocyanidins have another interflavan bond C2β!O7, and procyanidins A1, A2, B1, B2, B3 are dimers, procyanidin C1 is trimer [27]. Increasing evidence has demonstrated that procyanidin A1 has anti-inflammatory and anti-oxidative effects on LPS-stimulated RAW264.7 cells [9]. Procyanidin B1, B2, and C1 showed anti-inflammatory and oxidative activities in human monocytes [28].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…The result of study indicates LPS dramatically increases the production of pro-inflammatory cytokines such as NO, iNOS, IL-6, and TNF-α in RAW264.7 cells by activation of NF-κB and increases the expression and synthesis of inflammatory cytokines (TNF-α, IL-6, IL-1β, NO, and iNOS2). In the conclusion it was summarized that inhibition or disorder of NF-κB pathway could be potential target in the treatment of inflammation and oxidative stress (Han et al, 2019). Activated NF-κB regulates gene transcription related to host immune, inflammatory responses and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%